2011
DOI: 10.1002/jbmr.359
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1R signaling in chondrocytes modulates growth plate development by interacting with the PTHrP/Ihh pathway

Abstract: Systemic derangements and perinatal death of generalized insulin-like growth factor 1 (IGF-1) and IGF-1 receptor (IGF-1R) knockout mice preclude definitive assessment of IGF-1R actions in growth-plate (GP) chondrocytes. We generated cartilage-specific Igf1r knockout (CartIgf1r−/−) mice to investigate local control of chondrocyte differentiation in the GP by this receptor. These mice died shortly after birth and showed disorganized chondrocyte columns, delayed ossification and vascular invasion, decreased cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 37 publications
1
81
0
2
Order By: Relevance
“…The IGF1R has been deleted using the Col2a1, and its phenotype shows growth plate defects including disorganized chondrocytes, decreased proliferation and increased apoptosis. 33 The use of a tamoxifen inducible model to delete the IGF1R in chondrocytes 1 week postnatally revealed a significant reduction in growth plate chondrocyte proliferation and differentiation. 26 Recently, IGF-1 was deleted using the Hoxb6 cre (this cre is expressed in both the hind and anterior part of the forelimb) and the phenotype revealed a critical role for IGF-1 in controlling the size of the limbs through the volume of hypertrophic chondrocytes.…”
Section: Igf-1 and Chondrocytesmentioning
confidence: 99%
“…The IGF1R has been deleted using the Col2a1, and its phenotype shows growth plate defects including disorganized chondrocytes, decreased proliferation and increased apoptosis. 33 The use of a tamoxifen inducible model to delete the IGF1R in chondrocytes 1 week postnatally revealed a significant reduction in growth plate chondrocyte proliferation and differentiation. 26 Recently, IGF-1 was deleted using the Hoxb6 cre (this cre is expressed in both the hind and anterior part of the forelimb) and the phenotype revealed a critical role for IGF-1 in controlling the size of the limbs through the volume of hypertrophic chondrocytes.…”
Section: Igf-1 and Chondrocytesmentioning
confidence: 99%
“…We speculate that the decreased IGF1R/Akt signaling in bones of NO66-TG mice could contribute in part to the decreased mRNA expression of Runx2 and Osx, and this decrease may be then responsible for the decreased number of hypertrophic chondrocytes and Osx-expressing cells observed in these mice. In fact, the phenotype of our NO66-TG mice resembles that of cartilage-specific Igf1r knockout mice, which exhibit growth retardation with disorganized chondrocyte columns, delayed primary ossification, and decreased chondrocyte proliferation (14). We propose that the reduction of IGF1R/Akt signaling cascade in bones of NO66-TG mice contributes in part to the bone growth retardation phenotype of these mice.…”
Section: Discussionmentioning
confidence: 69%
“…7A, C; P , 0.05). These results suggested that mesenchymal overexpression of NO66 in mice may inhibit the IGF1/IGF1R/Akt signaling pathway, an important signal in the control of chondrocyte and osteoblast proliferation (14,15). Previous in vitro studies reported that NO66 has a histone demethylase activity that is specific for H3K4me3 and H3K36me3.…”
Section: Proliferation Of Skeletal Cells In No66-tg Micementioning
confidence: 81%
See 2 more Smart Citations